Correction: Melián-Ortíz et al. Superficial Neuromodulation in Dysautonomia in Women with Post-COVID-19 Condition: A Pilot Study. Brain Sci. 2025, 15, 510 - Alberto Melián-Ortíz; Eduardo Zurdo-Sayalero; Sara Perpiñá-Martínez; Antonio Delgado-Lacosta; Carmen Jiménez-Antona; Josué Fernández-Carnero; Sofía Laguarta-Val (Brain Sciences, 2025)
In the original publication, the affiliation was NEDECOR, which will be replaced by NECODOR [...]